Evaluation of the activities of healthcare organizations of the city of Minsk in providing medical care in hospital settings to patients with chronic obstructive pulmonary disease - D. I. Borodin; I. N. Moroz (Military Medicine, 2026)
This ar ticle examines the dynamic provision of inpatient medical care to patients with chronic obstructive pulmonary disease in Minsk healthcare facilities. From 2021 to 2024, the number of hospitalized patients with chronic obstructive pulmonary disease increased more than threefold. From 2017 to 2024, the average length of stay for patients with chronic obstructive pulmonary disease increased by 7.14 % (from 13.47 to 14.43 days). This increase in the average length of stay for patients with chronic obstructive pulmonary disease may indicate a predominance of patients with more severe forms of the disease, requiring longer inpatient treatment, and entails increased healthcare costs and an economic burden on the state.